Maximum Profit Feed Formulation 3. Interaction Between Energy Content and Temperature - Cerrate, Sandro; Waldroup, Park (International Journal of Poultry Science, 2010)
Nutritional models for comparison of environmental conditions on responses to dietary energy using data from literature were evaluated to formulate broiler diets by maximum profit feed formulation with real or simulated prices of corn and soybean meal. These diets were formulated based on Corn and Soybean Meal (C-SBM) or with Wheat and Cottonseed Meal (+W-CM) as alternative sources of energy and protein. Average body weight gain or feed intake slopes at normal temperature were significantly higher than those at heat stress. The rate of gain per calorie was two times higher at normal compared to heat stress and the rate of feed intake per calorie was half as high at normal than did at heat stress. At real or simulated prices, the economic energy content in most cases was reduced by heat stress compared to those at normal temperature. For real prices the energy reductions from normal temperature to heat stress were from 3.254 to 3.015 kcal/g for diets based on C-SBM or from 3.2 to 2.961 kcal/g for diets based on +W-CM. These economic energy reductions were around 7% from real prices, up to 10% from simulated corn prices and up to 9% from simulated SBM prices. The inclusion of +W-CM reduced the economic energy content and increased the profitability compared to those based on C-SBM diets. These data indicate that broiler diets fed during heat stress should be formulated with reduced economic energy content due to decreased rate of gain or feed intake per calorie compared to those at normal temperature.